The application of project management in residential housing construction (greenland housing case study) PT. kalimantan global property - Barus, Bela; Rachmawati, Indri; Fatimah, Fatimah; Esveranza, Andi (Enrichment : Journal of Management, 2025)
This study examines the application of project management in the construction of a two-story 72/90 type house in the Greenland Housing area by PT Kalimantan Global Property. The construction of a house, even though it is small-medium scale, still has high complexity, including budget constraints, tight schedules, and limited human resources. Therefore, effective project management is needed to ensure the efficiency and effectiveness of construction implementation. A qualitative descriptive case study is the research methodology employed, and data is gathered through project document analysis, interviews, and observation. The study’s findings show that using the Program Evaluation and Review Technique (PERT) and the Critical Part Method (CPM) methods can help plan, control, and evaluate project time more accurately. The project was successfully completed within 128 days of a total planning of 240 days without significant delays, with cost efficiency and good quality of work results. This study proves that a project management approach based on the network method can improve project performance, even for the construction of medium-scale houses. These findings emphasize the importance of systematic documentation, utilization of project management tools, and structured supervision as key factors for the success of construction projects